Thermo-Mechanical Behaviour of Structural Lightweight Alloys - Requena, Guillermo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The need to reduce the ecological footprint of water/land/air vehicles in this era of climate change requires pushing the limits regarding the development of lightweight structures and materials. This requires a thorough understanding of their thermomechanical behavior at several stages of the production chain. Moreover, during service, the response of lightweight alloys under the simultaneous influence of mechanical loads and temperature can determine the lifetime and performance of a multitude of structural components. The present Special Issue, comprising eight original research articles, is dedicated to disseminating current efforts around the globe aimed at advancing understanding of the thermomechanical behavior of structural lightweight alloys under processing or service conditions.